Peran Manajemen Perkantoran dalam Meningkatkan Kinerja Tenaga Pendidik di MTs Muallimin Univa Medan - Muhammad Ibnu; Khoiriyah Syaharani Ritonga; Maulana Harin Hanafi; Adhli Maulana; Tengku Darmansah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study investigated the role of office management in improving the performance of teaching staff at MTs Muallimin Univa Medan. The research findings revealed two main themes: (1) the efficiency of school administration in freeing teachers to focus on learning, and (2) effective communication as the foundation of good office management in schools. Efficient administrative management allows teachers to access student information quickly, simplifies reporting, and increases the transparency of communication with management. Open and transparent communication between leaders, administrative staff and educators also supports smooth coordination and collaboration. The results of this study emphasize the importance of effective office management in creating a work environment conducive to improving the quality of learning and student achievement.